Quantitative molecular plating of large-area 242Pu targets with improved layer properties. (January 2015) - Vascon, A.; Runke, J.; Trautmann, N.; Cremer, B.; Eberhardt, K.; Düllmann, Ch.E.
Abstract: For measurements of the neutron-induced fission cross section of 242 Pu, large-area (42 cm 2 ) 242 Pu targets were prepared on Ti-coated Si wafers by means of constant current density molecular plating. Radiochemical separations were performed prior to the platings. Quantitative deposition yields (>95%) were determined for all targets by means of alpha-particle spectroscopy. Layer densities in the range of 100–150 μg/cm 2 were obtained. The homogeneity of the targets was studied by radiographic imaging. A comparative study between the quality of the layers produced on the Ti-coated Si wafers and the quality of layers grown on normal Ti foils was carried out by applying scanning electron microscopy and energy dispersive X-ray spectroscopy. Ti-coated Si wafers resulted clearly superior to Ti foils in the production of homogeneous 242 Pu layers with minimum defectivity. Highlights: Large area (i.e., 42 cm 2 ) 242 Pu targets were prepared on Ti-coated Si wafers. Quantitative deposition yields (>95%) were obtained. Homogeneous 242 Pu layers with minimum defectivity were produced. The targets were prepared for future 242 Pu( n, f ) cross section measurements.